Correlation of Insulin Like Growth Factor-1 and Insulin-Like Growth Factor Binding Protein with LH, FSH and Testosterone in Iraqi Children with Growth Hormone Deficiency - Hasan, Athraa F.; Hassan, Bushra F.; AL-SAMERAIE, ABDILKAREEM Y. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Insulin like growth factor-1 has metabolic and growth-related roles all over the body and is strongly associated and regulated by growth hormone. It is produced by almost any type of tissue, especially the liver. The study aimed to measure insulin like growth factor in growth hormone deficient patients and find its relation with other studied parameters. The Subjects in the study were 180 studied in the National Diabetic Center for Treatment and Research/Al-Mustansiriya University in Baghdad/Iraq for the period from November 2021 to April 2022. Blood was drawn and investigated for the levels of IGF-1, IGFBP-3, LH, and FSH. Also testosterone and statistical analysis was carried out to find the potential correlations. The results relived that the gender was not affect the levels of either parameter, IGF-1 was found to be positively correlated with age, BMI, and IGFBP-3. While IGFBP-3 was found to be positively correlated with the levels of IGF-1, LH, FSH and testosterone. From the results of the current study, it can be concluded that the levels of GH as well as the levels of IGF-1 and IGFBP-3, have significant difference between the NGHD and the patients’ group.